Adjuvant chemotherapy-associated lipid changes in breast cancer patients: A real-word retrospective analysis. Issue 33 (14th August 2020) - He, Tao; Wang, Chengshi; Tan, Qiuwen; Wang, Zhu; Li, Jiayuan; Chen, Tao; Cui, Kaijun; Wu, Yunhao; Sun, Jiani; Zheng, Danxi; Lv, Qing; Chen, Jie
Abstract : Abstract: Adjuvant chemotherapy may cause alterations in serum lipids in postoperative breast cancer (BC) patients, but the specific alterations caused by different chemotherapy regimens remain unclear. The aim of this study was to investigate the status of serum lipids pre- and post-chemotherapy and to compare the side effects of different chemotherapy regimens on serum lipid. We retrospectively analysed the lipid profiles of 1934 consecutive postoperative BC patients who received one of the following chemotherapy regimens: doxorubicin and cyclophosphamide followed by paclitaxel (AC-T); epirubicin and cyclophosphamide followed by paclitaxel (EC-T); cyclophosphamide and paclitaxel (TC); and fluorouracil, cyclophosphamide, and epirubicin (FEC). The levels of triglycerides (TG), total cholesterols (TC), and low-density lipoprotein (LDL-C) were significantly elevated in patients who received chemotherapy regimens above ( P  < .001). With respect to different chemotherapy regimens, FEC had less side effects on lipid profiles (TG ( P   =  .006), high-density lipoprotein (HDL-C) ( P  < .001), and LDL-C ( P  < .001)) than TC regimen and AC-T and EC-T regimen. Also, the incidence of newly diagnosed dyslipidemia after chemotherapy was lower in FEC group than TC group and AC-T and EC-T group ( P  < .001). Additionally, the magnitude of the alterations in lipid profiles (TG, TC, HDL-C, and LDL-C) was greater in premenopausal patients than that of the postmenopausal patients ( P   =  .004; P  < .001; P   =  .002; P   =  .003, respectively). Moreover, after adjusting for multiple baseline covariates, anthracycline-plus-taxane-based regimens (AC-T and EC-T) were still statistically associated with a high level of TG ( P   =  .004) and a low level of HDL-C ( P   =  .033) after chemotherapy compared with FEC regimen. Also, body mass index (BMI) > 24 was associated with abnormal lipid profiles (TG, TC, HDL-C, LDL-C) post-chemotherapy compared with BMI ⩽ 24 ( P  < .001; P   =  .036; P   =  .012; P   =  .048, respectively). BC patients receiving chemotherapy may have elevated lipid profiles, and anthracycline-based regimen had less side effects on lipid profiles compared with regimens containing taxane. Therefore, it is necessary to take lipid metabolism into consideration when making chemotherapy decisions and dyslipidemia prevention and corresponding interventions are indispensable during the whole chemotherapy period.